Efficacité d’utilisation de podcast Coffee Break French pour améliorer la compétence de la compréhension orale des élèves de MAS YASPI Labuhan Deli Medan - Putri Sherlita; Junita Friska (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This research aims to determine the effectiveness of using the Coffee Break French podcast to improve the listening comprehension skills of students at MAS YASPI Labuhan Deli Medan. The study is based on the observation that students struggle to understand spoken French, primarily due to a lack of authentic teaching materials. The research uses a quantitative method with a pre-test/post-test experimental design on a single group. The sample comprises 32 students. The data collection instruments are a pre-test and a post-test. The results show a significant increase in the average scores, from 40.63 in the pre-test to 82.66 in the post-test. The paired t-test yields a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a statistically significant difference between the results before and after the treatment. In addition, the average normalized gain (N-Gain) is 70%, which is classified as ‘effective’ according to Arikunto's criteria. Thus, we can conclude that using the Coffee Break French podcast is efficacious in improving students' listening comprehension of the Se Présenter material.